Flies for the Pollination of Greenhouse Mango (Mangifera Indica L., Anacardiaceae) in the Subtropical Iriomote Island, Japan - Alqarni, AS; Ahmed, KN; Hannan, MA; Ghose, GK; Munshi, JL (Journal of the Asiatic Society of Bangladesh, Science, 2017)
Abstract Not Available Asiat. Soc. Bangladesh, Sci. 43(1): 135-141, June 2017